Perfil da prescrição de antibioticoprofilaxia em hospital público de Manaus - Melo, Felipe Leopoldo Costa de Sena (Brasil, 2020)
The rational use of prophylactic antibiotics (PA) through the follow-up of protocols is imperative to avoid infections in surgical sites, damage to the patient, associated costs, and microbial resistance. This study aimed to analyze the use of PA at the Getúlio Vargas University Hospital (HUGV) in 2017. Patient data, used in the Microsoft Excel® 2010 spreadsheet, from the HUGV Pharmacy Service, who used AP in 2017 were used. Univariate statistical analyzes of frequency distribution, calculation of central tendency, and dispersion were performed with the statistical program R version 3.1.2. The variables used were: date of attendance, clinic, bed, prescribed medication, concentration, dosage, indication, and time of use, according to the Standard Operating Procedure (POP) of HUGV Surgical The rational use of prophylactic antibiotics (PA) through the follow-up of protocols is imperative to avoid infections in surgical sites, damage to the patient, associated costs and microbial resistance. This study aimed to analyze the use of PA at the Getúlio Vargas University Hospital (HUGV) in 2017. Patient data, used in the Microsoft Excel® 2010 spreadsheet, from the HUGV Pharmacy Service, who used AP in 2017 were used. Univariate statistical analyzes of frequency distribution, calculation of central tendency, and dispersion were performed with the statistical program R version 3.1.2. The variables used were: date of attendance, clinic, bed, prescribed medication, concentration, dosage, indication, and time of use, according to the Standard Operating Procedure (POP) of HUGV Surgical Antibiotic Prophylaxis. Altogether 82.2% of the 2759 AP requests were in accordance with the POP. The surgical clinic was the source of most prescriptions (81.2%), of which 16.7% were inadequate. Cefazolin was the most requested medication (78%) followed by ceftriaxone and metronidazole, which had conformities in their prescriptions of 94.2%, 0%, and 75.6%, respectively. The main reasons for non-compliance were the use of non-standard antibiotics (49.07%) and use for more than 24 hours (36.72%). Regardless of the high adherence to the institution's Antibiotic Prophylaxis POP in 2017, it was observed that the cost of nonconformities (R$ 15,474.11), corresponding to 490 prescriptions, would be higher than the amount spent on prescriptions in conformity (R $ 14,822.95) in 2269 prescriptions.